(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Age-related problems are one of the most complex events in the voluntary sphere of a child’s life should be considered. In the article, there are various problems that children of primary school age have specific features of its manifestation are discussed.